Studi Literatur Tentang Kerja Sama Guru dan Orang Tua dalam Mengatasi Siswa Berkesulitan Belajar Membaca Permulaan - Anita Dewi Widyasworo; Mudzanatun Mudzanatun; Fajar Cahyadi (STKIP Andi Matappa Pangkep, 2022)
This study aimed to determine the efforts that can be made by teachers and parents in resolving the problem of reading difficulties and the inhibiting factors of the efforts of teachers and parents in resolving reading difficulties. The type of research used is a literature study research method with a qualitative approach. Data collection techniques using documentation and observation studies. The data analysis technique uses the Miles and Huberman stages, namely the data reduction stage, data presentation and conclusion drawing. The results of this study indicate that the efforts made by teachers and parents include using learning strategies or methods, providing supporting facilities for learning to read such as learning media, interesting reading books, building simple libraries at home and in classrooms, providing activities remedial for students with reading difficulties, always give a positive response, and provide learning assistance at home by parents. Factors inhibiting the efforts of teachers and parents include a learning atmosphere that is not conducive, students who experience sensory disturbances, low self-confidence, low student interest in reading, lack of existing learning facilities, no learning process at home, and the economic situation of parents is low.